Critical Discourse Analysis of Religious Moderation Values in Islamic Religious Education and Character Education Textbooks at the Junior High School Level - Robi Awaludin, Apriyanti, Munir, Zuhdiyah, Hamidah, Muhammad Torik, Indah Wigati, Maryamah, Leny Mar (Journal of Educational Studies, 2025)
The understanding of religious moderation has not yet been fully internalized. Islamic Religious Education and Character Education (PAI and BP) textbooks play a crucial role in instilling the values of religious moderation; however, inconsistencies between the narrative and the principles of moderation are still evident. This study aims to analyze the text, discursive practices, and socio-cultural practices related to the values of religious moderation in PAI and BP textbooks at the junior high school level. This research employs a qualitative method using Norman Fairclough’s critical discourse analysis framework. The findings indicate that, at the textual level, the sentence structures are manifested through both written text and images that emphasize tolerance and harmony among religious communities. However, there remains the use of exclusive diction that can lead to bias. At the level of discursive practice, the textbooks present values of religious moderation through Qur’anic verses, inspirational stories, narratives, images, and other supporting elements. These are further reinforced through discussions and case studies that relate to the diverse realities of students’ lives. At the level of social practice, the textbooks function as a medium of national ideology in shaping a moderate generation aligned with Indonesia’s pluralistic society.